Development and Validation of Prediction Formula of Wingate Test Peak Power From Force–Velocity Test in Male Soccer Players - Nikolaidis, Pantelis T.; Knechtle, Beat (Frontiers in Psychology, 2021)
Peak power of the Wingate anaerobic test (WAnT) - either in W (Ppeak) or in W.kg-1 (rPpeak) - has been used to evaluate performance of soccer players; however, its relationship with Force-velocity (F-v) test (e.g., whether these tests can be used interchangeably) has received little scientific attention. The aim of the study was to develop and validate a prediction equation of Ppeak and rPpeak from F-v characteristics in men soccer players. Participants were 158 adult men soccer players (sport experience 11.4±4.5 years, mean±standard deviation, ~five weekly training units, age 22.6±3.9 years, body mass 74.8±7.8 kg and height 178.3±7.8 cm) who performed both WAnT and F-v test. An experimental (EXP, n=79) and a control group (CON, n=79) were used for development and validation, respectively, of prediction equation of Ppeak and rPpeak from F-v test. In EXP, Ppeak correlated very largely with body mass (r=0.787), fat-free mass (r=0.765), largely with maximal power of F-v test (Pmax; r=0.639), body mass index (r=0.603), height (r=0.558), moderately with theoretical maximal force (F0; r=0.481), percentage of body fat (r=0.471), fat mass (r=0.443, p<0.001); rPpeak correlated with rPmax (largely; r=0.596, p<0.001), theoretical maximal velocity (v0; moderately; r=0.341, p=0.002), F0 (small magnitude; r=0.280, p=0.012), BF (r=-0.230, p=0.042) and fat mass (r=-0.242,p=0.032). Ppeak in EXP could be predicted using the for-mula '44.251 + 7.431 × body mass (kg) + 0.576 × Pmax (W) - 19.512 × F0' (R=0.912, R2=0.833, standard error of estimate, SEE=42.616) and rPpeak from '3.148 + 0.218 × rPmax (W.kg-1) + v0 (rpm)' (R=0.765, R2=0.585, SEE=0.514). Applying these formulas in CON, no bias was observed between actual and predicted Ppeak (mean difference 2.5±49.8 W; 95% CI, -8.7, 13.6; p=0.661) and rPpeak (mean difference 0.05±0.71 W.kg-1; 95% CI, -0.11, 0.21, p=0.525). These findings provided indirect estimates of Ppeak of the WAnT, especially useful in periods when this test should not be applied considering the fatigue it causes; in this context, the F-v test can be considered as an alternative of exercise testing for estimating the average Ppeak of a group of soccer players rather than for predicting individual scores when the inter-individual variation of performance is small.